2014
DOI: 10.1177/003335491412900211
|View full text |Cite
|
Sign up to set email alerts
|

Timely HIV Diagnosis and HIV/TB Comanagement among California Patients in 2008

Abstract: Objective. National guidelines highlight the roles of early HIV diagnosis and effective comanagement for HIV and tuberculosis (TB) to prevent mortality and morbidity from HIV-related TB. We assessed HIV diagnosis timing and HIV/TB comanagement for California HIV/TB patients.Methods. We reviewed and analyzed public health charts for California HIV/TB patients reported during 2008. HIV diagnoses fewer than three months before TB diagnosis were considered new HIV diagnoses. We determined the proportion of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Along with efforts to make progress on each outcome on the "HIV care cascade", the Joint United Nations Programme on HIV/AIDS (UNAIDS) calls for making equitable progress on HIV outcomes and addressing HIV-related disparities by devising focused prevention and treatment programs for key populations [1]. One population of interest is foreignborn persons living in the US, who have an increased risk of exposure to HIV and higher rates of HIV incidence [2,3]. Previous studies comparing US-born and foreign-born persons have found that the epidemiology of HIV among foreign-born persons living in the US is complex and involves risk factors related to immigration, education, and health care.…”
Section: Introductionmentioning
confidence: 99%
“…Along with efforts to make progress on each outcome on the "HIV care cascade", the Joint United Nations Programme on HIV/AIDS (UNAIDS) calls for making equitable progress on HIV outcomes and addressing HIV-related disparities by devising focused prevention and treatment programs for key populations [1]. One population of interest is foreignborn persons living in the US, who have an increased risk of exposure to HIV and higher rates of HIV incidence [2,3]. Previous studies comparing US-born and foreign-born persons have found that the epidemiology of HIV among foreign-born persons living in the US is complex and involves risk factors related to immigration, education, and health care.…”
Section: Introductionmentioning
confidence: 99%